PENGARUH GAYA BELAJAR TERHADAP PRESTASI AKADEMIK SISWA DI MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM MTs AL-KAUTSAR DEPOK - Muh Fauzan Nastiar; Salsabila Wulandari, Syahdan Ambrifa, Iris Agripina Zen (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study aims to analyze the influence of learning style on students' academic achievement in the subject of Islamic Cultural History (ICH) at MTs Al-Kautsar, Depok. Learning styles include three main types, namely visual, auditory, and kinesthetic, each of which affects the way students understand and process information. Academic achievement is measured based on the results of student learning evaluation in SKI subjects. This study uses a quantitative approach with a survey method. Data was collected through questionnaires to identify students' learning styles and documentation of learning outcome values as indicators of academic achievement. The results of the study show that learning style has a significant influence on students' academic achievement. Students with visual learning styles tend to excel in understanding the material presented through images, diagrams, and concept maps. Meanwhile, students with auditory learning styles are more successful when learning involves discussion or verbal explanation. The kinesthetic learning style provides an advantage in activities that involve hands-on practice or simulation. Based on these findings, it is recommended that SKI teachers at MTs Al- Kautsar adopt diverse learning strategies to accommodate all types of learning styles, so as to improve overall academic achievement.